Down-regulation of serotonin and dopamine transporter genes in individual rats expressing a gambling-prone profile: A possible role for epigenetic mechanisms. (6th January 2017) - Zoratto, Francesca; Romano, Emilia; Pascale, Esterina; Pucci, Mariangela; Falconi, Anastasia; Dell'Osso, Bernardo; Maccarrone, Mauro; Laviola, Giovanni; D'Addario, Claudio; Adriani, Walter
Highlights: Epigenetic mechanisms may play a role in Gambling Disorder. Rats underwent an operant protocol for evaluation of individual propensity to gamble. We investigated 5-HT and DA systems at both central and peripheral levels. Experience of a gambling task induced selective gene down-regulation in rats. Methylation of SERT gene was increased in the PFC of rats with a "gambler" phenotype. Abstract: Gambling Disorder (GD) is characterized by excessive gambling despite adverse consequences on individual functioning. In spite of some positive findings, it is difficult to draw any conclusion on the genetics of GD. Indeed, beyond DNA sequence variation, other regulatory mechanisms (like those that engage epigenetics) may explain gene alterations in this addictive disease. Wistar male rats underwent an operant task for the evaluation of individual propensity to gamble. Few rats, after having learnt to prefer nose-poking for a large over a small food reward, were sacrificed to obtain a baseline profile of gene expression at both central and peripheral levels. In the remaining rats, probability of occurrence of large-reward delivery decreased progressively to very low levels. Thus, rats were faced with temptation to "gamble", i.e. to nose-poke for a binge reward, whose delivery was omitted the majority of times. After 3 weeks of testing, rats showing a clear-cut profile of either gambling proneness or aversion were selected and sacrificed after the last session. A selective down-regulation of i) serotonin transporter in prefrontal cortex, ii) tyrosine hydroxylase in ventral striatum, iii) dopamine transporter in lymphocytes was evidenced in "gambler" vs "non-gambler" rats. The exposure to such operant task (compared to home-cage alone) modulated ventrostriatal but not prefrontal genes. A consistent increase of DNA methylation, in one specific CpG site at serotonin transporter gene, was evident in prefrontal cortex of "gambler" rats. Elucidation of epigenetic changes occurring during GD progression may pave the way to the development of new therapeutic strategies through specific modulation of epigenetic factors.